2007
DOI: 10.1007/s00265-007-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

The lemur syndrome unresolved: extreme male reproductive skew in sifakas (Propithecus verreauxi), a sexually monomorphic primate with female dominance

Abstract: The primates of Madagascar (Lemuriformes) are unusual among mammals in that polygynous species lack sexual dimorphism, and females dominate males socially in most species. Moreover, lemur groups are relatively small and characterized by even adult sex ratios despite the fact that one male should be able to exclude other males from the group. One hypothesis to explain this combination of behavioral, morphological, and demographic traits (the "lemur syndrome") postulates that male-male competition is relaxed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 87 publications
4
85
0
Order By: Relevance
“…As a consequence of both the high degree of male reproductive skew seen at Lomas and the stability in male alpha rank, alpha status is an excellent marker of the paternal descent of infants in this population. In another primate with extreme male reproductive skew toward alpha males, Verreaux's sifakas (Propithecus verreauxi), dominant non-natal males residing in groups containing other non-natal adult males sire approximately 91% of offspring (Kappeler & Schäffler, 2008). Alpha male status should thus also be an informative marker for close relatedness, and more specifically paternity in these sifakas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of both the high degree of male reproductive skew seen at Lomas and the stability in male alpha rank, alpha status is an excellent marker of the paternal descent of infants in this population. In another primate with extreme male reproductive skew toward alpha males, Verreaux's sifakas (Propithecus verreauxi), dominant non-natal males residing in groups containing other non-natal adult males sire approximately 91% of offspring (Kappeler & Schäffler, 2008). Alpha male status should thus also be an informative marker for close relatedness, and more specifically paternity in these sifakas.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha male status should thus also be an informative marker for close relatedness, and more specifically paternity in these sifakas. Indeed, there is some evidence for later father-daughter discrimination in the species in the form of inbreeding avoidance (Kappeler & Schäffler, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of reproducing females within a group is small (1-3 individuals; Kubzdela 1997;Lewis 2005;Richard et al 2002), dominant males do not exclude rival males from group membership, resulting in a tendency toward an even adult sex ratio. Despite the presence of multiple males within groups, according to genetic paternity analysis, reproduction in the Kirindy Forest population is highly skewed in favor of dominant individuals with dominant males siring almost all offspring (91% of 33 infants; Kappeler and Schäffler 2008). In contrast, paternity analysis results for a population of Propithecus verreauxi at Beza Mahafaly revealed that extragroup fertilizations occur more frequently (Lawler 2007).…”
mentioning
confidence: 64%
“…We studied 9 groups of well habituated sifakas living in one of these study areas. All individuals in the study population are marked with either unique nylon collars and pendants or radio collars (Kappeler and Schäffler 2008). Group size and composition varied across the 9 study groups over the 2 sampling periods (Table I).…”
Section: Study Site and Populationmentioning
confidence: 99%